PENGEMBANGAN INFRASTRUKTUR DAN KEBIJAKAN PUBLIK GUNA MENDUKUNG PERTUMBUHAN EKONOMI KREATIF DI NEGARA BERKEMBANG - Mutafikatul Khoiriyah; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
. This research aims to explore the relationship between physical infrastructure, institutional infrastructure, public policy, and creative economic growth in developing countries. The research method used is quantitative with a cross-sectional approach, involving populations of creative economy actors in four developing countries—Indonesia, Vietnam, Kenya and Brazil. Data was collected through surveys and in-depth interviews, and analyzed using multiple linear regression techniques. Research findings show that physical infrastructure, institutions and public policies significantly contribute to increasing creative economic growth. Investment in adequate infrastructure and strengthening conducive public policies have proven effective in increasing the productivity and competitiveness of the creative economy sector. The implications of this research are important for policy makers to formulate more effective strategies in supporting the creative economy in developing countries, with an emphasis on integrating various aspects of infrastructure and policy to achieve optimal results.